Mandibular distraction of free iliac crest bone graft as treatment in a patient with a history of gunshot wound. Case Report - Jaime Andrés Jiménez-Álvarez; Jesus Andrés Duque-Montealegre; José Manuel Valdés-Reyes (Case Reports)
Introduction: The combination of non-vascularized iliac crest bone graft and distraction osteogenesis in a second surgical intervention has only been described to achieve alveolar ridge augmentation. This technique is not recommended to treat bone defects of the jaws caused by firearm projectile.